2017
DOI: 10.4081/hr.2017.7406
|View full text |Cite
|
Sign up to set email alerts
|

Expression of some ATP-binding cassette transporters in acute myeloid leukemia

Abstract: Hematopoietic cells express ATP binding cassette (ABC) transporters in relation to different degrees of differentiation. One of the known multidrug resistance mechanisms in acute myeloid leukemia (AML) is the overexpression of efflux pumps belonging to the superfamily of ABC transporters such as ABCB1, ABCG2 and ABCC1. Although several studies were carried out to correlate ABC transporters expression with drug resistance, little is known about their role as markers of diagnosis and progression of the disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Activation of NF-κB or/and overexpression of ABC transmembrane proteins play a major role in the resistance of tumor cells to chemotherapy [2][3][4]. Many chemotherapeutic agents, including 5-FU, doxorubicin, etoposide or cisplatin have been reported to activate NF-κB and to upregulate expression of ABC transporters [37][38][39][40]. In several cancer cell lines the inhibition of either NF-κB or ABC transporter activity increased intracellular accumulation of chemotherapeutic drugs [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NF-κB or/and overexpression of ABC transmembrane proteins play a major role in the resistance of tumor cells to chemotherapy [2][3][4]. Many chemotherapeutic agents, including 5-FU, doxorubicin, etoposide or cisplatin have been reported to activate NF-κB and to upregulate expression of ABC transporters [37][38][39][40]. In several cancer cell lines the inhibition of either NF-κB or ABC transporter activity increased intracellular accumulation of chemotherapeutic drugs [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in cancer research, chemotherapy remains the first-line treatment for AML, the efficacy of which is limited by the development of MDR. The overexpression of drug-efflux pumps has been implicated in the failure of AML chemotherapy, causing disease refraction or relapse (27). Therefore, substances that are capable of restoring chemosensitivity are continuously being investigated to maintain cytotoxicity and the clinical response of chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that P-glycoprotein (P-gp) overexpression in tumor tissues is the major mechanism of MDR, yet it is not the solely mechanism. Rising researches revealed that MDR-associated proteins (MRPs), members of ABC transporter superfamily, play important parts in cellular multidrug resistance [24, 25]. MRPs chiefly exist in the plasma membrane and seem to act as a drug pump which can reduce cellular drug levels, resulting in cellular multidrug resistance [24].…”
Section: Discussionmentioning
confidence: 99%